2018
DOI: 10.4209/aaqr.2017.03.0112
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Sources, and Health Risk Assessment of Trace Elements in PM10 at an Urban Site in Chengdu, Southwest China

Abstract: To investigate trace element pollution of PM 10 in urban Chengdu, a Southwest megacity of China, as well as to assess the human health risks caused by exposure to PM 10 , we analyzed ambient PM 10 samples collected at an urban site in Chengdu from November, 2014 to October, 2015. The annual mean concentration of PM 10 in the sampling period was 173.6 ± 77.9 µg m -3 , which is 2.5 times higher than the national recommended standard of 70 µg m -3 . The mean metals content in PM 10 was in the following order:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…The elemental concentrations emerged in the present study were found to be higher than the nationwide inventories from (Faisalabad [36], Lahore [37], Islamabad [38]). The concentrations were also found higher than the reports from international cities such as (Dhaka [39], Chengdu [40], Istanbul [41], Milan [42]). https://doi.org/10.37358/RC.20.2.7928…”
Section: Elemental Concentrationscontrasting
confidence: 67%
“…The elemental concentrations emerged in the present study were found to be higher than the nationwide inventories from (Faisalabad [36], Lahore [37], Islamabad [38]). The concentrations were also found higher than the reports from international cities such as (Dhaka [39], Chengdu [40], Istanbul [41], Milan [42]). https://doi.org/10.37358/RC.20.2.7928…”
Section: Elemental Concentrationscontrasting
confidence: 67%
“…Increased concentrations of Al, Ba, Ca, Fe, Mg and Ti especially for PM2.5 fraction were found, which could indicate resuspension of soil dust in spring. Al, Ba, Fe, Mg and Ti comes predominantly from soil dust, and their emission is increased in warmer periods (Nordberg et al, 2015;Titos et al, 2014;Sarti et al, 2014, Rudnick andGao, 2003;Cheng et al, 2018). For Al, Ba, Ca, Mg and Ti the lowest concentrations were observed in winter or autumn.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Remarkably, they also found out that Cr(VI) is carcinogenic and has the potential to cause asthma, liver damage, and nasal septum perforation (Banu et al, 2017;Oruko et al, 2020). Furthermore, Ni may lead to nasal and lung cancer (Cheng et al, 2018). In most cases, Cr species can get into the eukaryotic system and cause impulsive reactions with the intracellular reductants, for instance, ascorbate and glutathione, causing the short-lived intermediates Cr(V) and/or Cr(IV), free radicals and the Cr(III) endproduct (Oruko et al, 2020).…”
Section: Variations In Metallic Elements Concentrations and Contributmentioning
confidence: 99%
“…It is commonly acknowledged that there is no standard method for regulating the worn metal content in lubricating oils, although this evidence is believed to be beneficial by most vehicle operators and owners (Watson, 2010). There are two techniques commonly used for the determination of worn metallic species in lubricating oils (Cheng et al, 2018). Spectrometric analysis provide data on the composition of metallic species emanating from wear on engine components and/or from contamination and also from the metallic salts' concentration in additives.…”
Section: Variations In Metallic Elements Concentrations and Contributmentioning
confidence: 99%